Analysis of collision dynamics of lifting the pantograph during vehicle operation. (August 2022) - Yao, Yongming; Zhou, Ning; Mei, Guiming; Zhang, Weihua
It is a practical engineering problem to lift the pantograph during train operation. In this paper, a pantograph-catenary (PAC) model is established, which can realize pantograph lifting during train operation. In this model, the contact model between contact piece and contact wire is established using the polygon contact model (PCM). The PAC collision test rig is established, and the simulation model at low speed is verified by comparing the contact force and vertical acceleration of contact piece obtained from simulation and test. The factors influencing the process of pantograph lifting are analyzed. The simulation results show that the position where the dropper and contact wire are connected is the most disadvantageous position for pantograph lifting. The maximum impact force increases with the increase of pantograph lifting speed, and the relationship between them is linear. In addition, if the influence of aerodynamic force is not considered, the running speed of vehicle will not affect the pantograph lifting process.